A longitudinal analysis of some Australian broadacre farms' greenhouse gas emissions, farming systems and efficiency of production. (July 2016) - Kingwell, Ross; Marie Jeanne, Rose; Hailu, Atakelty
Abstract: This study tracks the emissions of 250 rainfed broadacre farms in south-western Australia from 2002 to 2011. Relationships between their emissions, farming systems, their productive efficiency and profit efficiency are examined. Emissions varied greatly among the farms, ranging from 0.02 to 2.49 CO2 -e tonnes per hectare, and averaged 0.43 CO2 -e tonnes per hectare. The distribution of emissions was rightwards skewed due to a small proportion of the sample being livestock dominant farms that generated high levels of emissions per hectare. The mix of enterprises on farms and the regional location of farms led to large differences being observed regarding farm aggregate and per hectare emissions. The trajectory of the farm emissions over the ten years was quadratic, with the diminution of emissions being attributable to the increased crop dominance of farming systems over the study period, an associated reduction in sheep numbers and the impacts of drought. The lessening in emissions towards the end of the decade occurred despite there being no policy incentive to lessen farm emissions. If these farms had to pay for their emissions then livestock farms in particular would have little capacity to pay. Across the decade, improvements in profit efficiency were significantly associated with only small increases in emissions per hectare. A 1% improvement in profit efficiency resulted in only a 0.10% increase in emissions per hectare. The implication is that improvements to the productive and profit efficiency of farms, although important for the commercial success of farming, are unlikely to cause large increases in farm emissions. Choice of the farm's enterprise mix and farm location are the more important decisions affecting farm emissions. Highlights: Farming system changes are helping lessen emissions on some Australian farms. Fewer sheep on many mixed enterprise farms is reducing farm emissions. Improving profit efficiency increases emissions only slightly. Choice of farm location and farming system is the main impact on emissions. New technologies or policies are needed to further reduce farm emissions.